SHORT OVERVIEW OF CLINICAL TRIALS WITH CURRENT IMMUNOTHERAPEUTIC TOOLS FOR CANCER TREATMENT - T. S. Nepomnyashchikh (SPb RAACI, 2017)
Over last decade, a substantial progress has been made, with respect to understanding of cancer biology and its interplay with the host immune system. Different immunotherapeutic drugs based on recombinant cytokines and monoclonal antibodies are widely used in cancer therapy, and a large number of experimental cancer treatments have been developed, many of which are currently undergoing various stages of clinical trials. Recent endorsement of a recombinant oncolytic herpesvirus T-VEC for the treatment of melanoma was an important step towards a more safe and efficient anticancer therapeutics. In this review, we shall mention only some of the most promising cancer immunotherapy strategies, namely, immune checkpoint inhibitors, cellular therapy and oncolytic viruses.